Penggunaan Metode Cooperative Integrated Reading And Composition (CIRC) Untuk Meningkatkan Keterampilan Membaca Pemahaman Bahasa Arab Siswi Kelas VIII Aisyah Semester Genap Di SMP Quran Darul Fattah Bandar Lampung Tahun Pelajaran 2019/2020 - Sutikno; Doni Sastrawan; Adam Sugiarto; Diah Asih (An Naba, 2021)
The Use of Cooperative Integrated Reading and Composition (CIRC) Method to Enhance Arabic Reading Comprehension Skills for Students of VIII Aisyah Class in Even Semester at Darul Fattah Quran Junior High School of Bandar Lampung in the 2019/2020 Academic Year ABSTRACT Regarding the development of education that continues to change and for the sake of developing education quality, one of the elements that must be considered in the educational curriculum is a foreign language. In Indonesia, Arabic is a foreign language; in keeping with the need, the Arabic language is taught more seriously alongside knowledge teaching. Nevertheless, learning a foreign language (Arabic) is not as easy as learning the mother tongue. Some obstructions must be coped with, such as ashwat science, grammar, and vocabulary. In addition, difficulties also come from students or teachers themselves, learning methods, materials, and teaching facilities. Therefore, the author examines students' reading comprehension skills with the research title “The Use of Cooperative Integrated Reading and Composition (CIRC) Method to Enhance Arabic Reading Comprehension Skills for Students of VIII Aisyah Class in Even Semester at Darul Fattah Quran Junior High School of Bandar Lampung in the 2019/2020 Academic Year” The type of research employed was Classroom Action Research (CAR). This research was carried out at Darul Fattah Quran Junior High School, Bandar Lampung, in Arabic class VIII subjects in the even semester of the 2019/2020 academic year. The study results revealed that using the Cooperative Integrated Reading and Composition (CIRC) method could enhance students' Arabic reading comprehension skills as evidenced by the mean value obtained in the first cycle of 76.82, categorized as adequate. However, it experienced a slight decrease of 0.30 points, equivalent to 0.39% in the second cycle, to 76.52 categorized as adequate. After that, cycle III underwent a relatively good increase of 4.95 points or equivalent to 6.47% to 81.47, with a sufficient category. Keywords: CIRC, Reading Comprehension Skill